2017
DOI: 10.1016/j.ceramint.2017.03.210
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of porosity level and pore former type on the mechanical and corrosion resistance properties of agro-waste shaped porous alumina ceramics

Abstract: The strength integrity and chemical stability of porous alumina ceramics operating under extreme service conditions are of major importance in understanding their service behavior if they are to stand the test of time. In the present study, the effect of porosity and different pore former type on the mechanical strength and corrosion resistance properties of porous alumina ceramics have been studied. Given the potential of agricultural wastes as pore-forming agents (PFAs), a series of porous alumina ceramics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Talou et al 24 reported the fabrication of macroporous mullite ceramics having total porosities and pore sizes within the ranges of 39%-44% and 10-70 µm, respectively, using starches from cassava, corn, and potato as PFAs. Also important to note is the existence of some reports, [25][26][27][28] including our previous investigations 27,28 on the utilization of agricultural waste materials, especially rice husk and sugarcane bagasse for preparing porous ceramic materials having total porosities, pore sizes, and tensile strengths within the ranges of 44%-67%, 70-178 µm, and 20.4-1.5 MPa, respectively. Generally, the mechanical properties in the investigations above demonstrated an inverse relationship with the total porosity and pore size parameters.…”
Section: Dele-afolabi Et Almentioning
confidence: 99%
“…Talou et al 24 reported the fabrication of macroporous mullite ceramics having total porosities and pore sizes within the ranges of 39%-44% and 10-70 µm, respectively, using starches from cassava, corn, and potato as PFAs. Also important to note is the existence of some reports, [25][26][27][28] including our previous investigations 27,28 on the utilization of agricultural waste materials, especially rice husk and sugarcane bagasse for preparing porous ceramic materials having total porosities, pore sizes, and tensile strengths within the ranges of 44%-67%, 70-178 µm, and 20.4-1.5 MPa, respectively. Generally, the mechanical properties in the investigations above demonstrated an inverse relationship with the total porosity and pore size parameters.…”
Section: Dele-afolabi Et Almentioning
confidence: 99%
“…They have been utilized to produce separation membranes, thermal insulation systems, catalyst supports, implantable bioceramics, and other uses. In particular, porous alumina ceramics—as one of the most popular oxide ceramics—have been used for a wide range of applications, including: separation materials, membranes, and implantable bioceramics . Nowadays, it has been prepared by various methods, including: freeze‐casting, chemical foams method, extrusion molding, and pore‐forming agent method …”
Section: Introductionmentioning
confidence: 99%
“…In addition, porous alumina ceramic has many important uses, for example, in electrode materials for fuel cells as well as catalyst carriers in the oil and chemical industries. 6 In these applications, thermal conductivity plays a vital role in heat transfer and is of general interest, especially in terms of effectively tailoring thermal conductivity as needed in the case of not affecting its use. Thus, the correlation between the pore structure parameters (eg, porosity, pore size, shape, distribution, connectivity, etc) and the thermal conductivity of porous ceramics as well as the prediction of thermal conductivity in specific environments or structures have been reported by different researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight porous materials find applications in diverse areas such as thermal insulation of high temperature industrial furnaces or exterior building walls, 1,2 filtration of hot and corrosive media, 3 ceramic membranes and its porous supports, 4 and radiant burners, 5 owing to their excellent properties such as low thermal conductivity, high porosity, high internal surface area, and specific pore structure. The alumina ceramic phase is important to the lightweight porous materials system due to the alumina phase has good mechanical and thermal properties 6,7 such as high mechanical strength, good chemical stability, and high service temperature. In addition, porous alumina ceramic has many important uses, for example, in electrode materials for fuel cells as well as catalyst carriers in the oil and chemical industries 6 .…”
Section: Introductionmentioning
confidence: 99%